Sugar Kelp (Saccharina latissima) Inhibits Hepatic Inflammation and Fibrosis with Increased Metabolic Rates in a Mouse Model of Diet-induced Nonalcoholic Steatohepatitis (OR24-08-19). (13th June 2019) - Kim, Mi-Bo; Lee, Yoojin; Bae, Minkyung; Kang, Hyunju; Hu, Siqi; Pham, Tho; Lee, Ji-Young; Park, Young-Ki
Abstract: Objectives: We investigated whether consumption of sugar kelp, an edible brown seaweed, can attenuate metabolic disturbances and nonalcoholic steatohepatitis (NASH) in a mouse model of NASH with evident liver fibrosis. Methods: Male C57BL/6 J mice were fed a low-fat control (LF; 6% fat by wt), a high-fat/high-sucrose/high-cholesterol control (HF; 34% fat, 34% sucrose, 2.0% cholesterol by wt), or a HF containing sugar kelp (HF-Kelp; 6.0% dried sugar kelp powder by wt) for 14 weeks. Blood chemistry as well as biochemical, molecular, and histological analyses were conducted in the liver and epididymal white adipose tissue (eWAT). Metabolic rates, energy expenditure, and physical activity of mice were determined using indirect calorimetry Results: Body weight of mice fed HF-Kelp was significantly lower than that of HF group. Compared to LF, HF significantly increased serum total cholesterol and glucose, which were decreased by kelp. In the liver, HF-Kelp group showed decreases in weight, triglycerides, total cholesterol, and steatosis compared with HF-fed mice. Also, kelp decreased hepatic expression of a macrophage marker F4/80 and an M1 macrophage marker CD11c. Mice fed HF-Kelp also exhibited decreased liver fibrosis as evidenced by less expression of fibrogenic genes and collagen accumulation than those of HF group. In eWAT, HF-Kelp diet reduced weight and adipocyte size compared with HF control. While HF-Kelp diet increased mRNA abundance of peroxisome proliferator activated receptor γ, it decreased the expression of collagen type VI alpha 1 chain, F4/80, CD11c, and tumor necrosis factor α, in eWAT. Oxygen consumption, carbon dioxide production, energy expenditure, and physical activity were significantly higher in HF-Kelp group than HF. Conclusions: Kelp consumption markedly prevented weight gain, fat accumulation, inflammation, and fibrosis in the liver and eWAT of mice with NASH. The health benefits of kelp were accompanied by increased metabolic rates, energy expenditure, and physical activity. Therefore, kelp may be consumed to prevent obesity-associated metabolic disturbances and NASH. Funding Sources: This study was supported by USDA Hatch.